Flora of Espírito Santo: Hiraeoide and Malpighioide clades (Malpighiaceae) - Paulo Henrique Dettmann Barros; Rafael Felipe de Almeida; Valquíria Ferreira Dutra (Rodriguésia, 2023)
Abstract This is a taxonomic treatment of four genera and eight species of the hiraeoide and malpighioide clades (Malpighiaceae) in the state of Espírito Santo, Brazil. Hiraea and Mascagnia are the most diverse genera, with three species each, followed by Amorimia and Lophopterys, with one species each. Two species are listed as threatened: H. bullata and M. velutina. The main characteristics that can be used to identify the genera in Espírito Santo are epipetiolar or interpetiolar stipules, the indumentum on the branches, the inflorescence type, the number of elaiophores, and characteristics of the mericarps. Morphological descriptions, identification keys, taxonomic notes, geographic distribution maps, and photographic plates are provided for the species.